IMUNOPATOGENESIS DAN MARKER VIRUS HEPATITIS B - Budi Darmanta Sembiring; Hendrika Andriana Silitonga (Majalah Ilmiah METHODA, 2018)
Hepatitis B is a sistemic disease which causes infection and necrosis so that it is important to understand about immunophatology and the check meaning of hepatitis B serology markers, expectl liver function test. By doing the serology test can be known the etiology of liver disease besides can be also used to determine the diseases status, also controlling the course of disease and the treatment and also useful from the epidemiology terms. The technique done by examiner of marker Hepatitis B based WHO by method of Radio immuno Assay (RIA), Enzyme linked immuno sorbent Assay (ELISA), Antibody monoclonal